Quantification of Airborne Noise Transmission in the Interior of an Ambulance. Issue 3 (September 2013) - Oliveira, Rafaela C.; Magalhaes, Max D. C.; Casas, Estevam B. Las; Santos, Juliana
Although the ambulances are designed for the purpose of taking a patient to the hospital at the least amount of time, apart from initial medical response and stabilisation, it is believed that no particular investigation has been made in order to analyse the noise level inside the ambulances in Brazil. It is well known that patients are stressed by the noise generated inside the cabin during ambulance transport. The focus of this paper is on the aspects of experimental tests for airborne sound transmission through ambulance panels and data for validation of predictive models found in the literature. An average reverberation time of 0.37 s was found for the ambulance cabin. The speech intelligibility in the cabin without any external noise (e.g. siren, traffic, ambulance motor, etc.) was assessed by measuring the Speech Intelligibility Index (STI) which was equal to 0.87, which is considered good for an adequate communication between paramedics and patients. The amount of airborne noise insulation provided by the left-hand side and rear façades was measured using the standardized level difference D 1 m, nt which was equal to 23 dB(A) and 13 dB(A) respectively.